(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2024)
Low-lying coasts are specially conditioned for the origin and development of coastal lagoons. The Pampean region (Buenos Aires, Argentina) contains the surplus of a sea level fluctuation that occurred during the last 6000 years. This report studied three coastal lagoons at different stages of their evolution: Mar Chiquita coastal lagoon, Las Brusquitas estuarine lagoon, and the small coastal lagoon of Balneario Reta. The long-term evolution is considered in the case of Mar Chiquita and Las Brusquitas, while modern trends are also described for the Mar Chiquita silting problems and the urbanisation of the Reta village surrounding the lagoon. The study is based on radiocarbon datings, salinity analyses and sedimentological studies on both outcrops and piston cores. At Mar Chiquita coastal lagoon, a shallow open bay has been restricting since the Middle Holocene, causing the development of marshes and tidal flats between cheniers and regressive spits. Its evolution is therefore conditioned to high-energy events that reworked bioclastic sands (cheniers and regressive spits) and the silting of fine sediments. The sequence outcropping at the outlet of the Las Brusquitas creek extended temporally between 6190 and 2380 14C years BP; the estuarine lagoon was located at the outlet of two creeks. New outcrops exhumed and radiocarbon datings indicated this new interpretation of the site as an estuarine lagoon silted in the last 2000 years. The small estuarine lagoon (“microalbufera”) of Balneario Reta is another wetland flooded by the increase in water discharge due to artificial channels. Their connection to the sea depends on the effects of maximum tides and winds blowing from the south. The contents in diatom assemblages were interpreted as indicators of changes in salinity balances during the Late Holocene. Oligohaline specimens dominated at the three coastal lagoons; polihaline and mesohaline assemblages characterise some intervals at the Mar Chiquita and Las Brusquitas sedimentary sequences. In order to preserve these coastal lagoons and the natural reserves related, it is necessary to preserve their dynamics according to forecasted sea level rise, and the water balances between salt and fresh waters.